2016
DOI: 10.1002/ep.12359
|View full text |Cite
|
Sign up to set email alerts
|

Reaction performance study on denitration in aqueous solution of the dual oxidant (H2O2/S2)

Abstract: The reaction performance study on NO removal by using the dual oxidant (H 2 O 2 /S 2 O 22 8 ) solution was carried out in self-designed bubbling reactor. The experimental results showed that NO removal efficiency was up to 92.9% at pH 11. The results of the thermodynamics calculation verified that NO removal by using strong alkaline dual oxidant (H 2 O 2 /S 2 O 22 8 ) solution was feasible. The results of the kinetic study showed that the reaction between NO and dual oxidant (H 2 O 2 /S 2 O 22 8 ) in strong al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…1-2), which is an oxidant with a similar function to • OH. Adewuyi et al [5,12] studied the In our previous studies [22,23] , we also showed that the combination of S 2 O 8 2and H 2 O 2 had a significant synergistic effect on NO removal. In addition, the NO removal efficiency under alkaline conditions was much higher than that under acidic or neutral conditions, reaching 80 % or higher for a long period of time under strongly alkaline conditions adjusted by the addition of sodium hydroxide (NaOH).…”
Section: Several Denitration Techniques Have Been Developed To Control Emissions Of No Xmentioning
confidence: 67%
See 1 more Smart Citation
“…1-2), which is an oxidant with a similar function to • OH. Adewuyi et al [5,12] studied the In our previous studies [22,23] , we also showed that the combination of S 2 O 8 2and H 2 O 2 had a significant synergistic effect on NO removal. In addition, the NO removal efficiency under alkaline conditions was much higher than that under acidic or neutral conditions, reaching 80 % or higher for a long period of time under strongly alkaline conditions adjusted by the addition of sodium hydroxide (NaOH).…”
Section: Several Denitration Techniques Have Been Developed To Control Emissions Of No Xmentioning
confidence: 67%
“…While the free radicals might be captured by O 2 [33] , the oxidation and absorption of NO was also promoted by O 2 (See Eqs. [22][23]. The effect of O 2 concentration on NO removal efficiency was less obvious.…”
Section: Effects Of Temperature and Ph On No Removalmentioning
confidence: 96%
“…It can be seen from Figure that the apparent activation energy of the NO removal by wet scrubbing using the oxidative absorbent S 2 O 8 2‐ /CaO 2 is 53.0 kJ/mol based on Equation . In previous research, the apparent activation energies of the NO removal using a NaClO 2 solution, an H 2 O 2 /Na 2 S 2 O 8 strong alkali solution, and an H 2 O 2 /NaOH solution were 42.5, 26.3, and 27.8 kJ/mol, respectively . These results show that the apparent activation energy of the NO removal by wet scrubbing using the oxidative absorbent S 2 O 8 2‐ /CaO 2 is higher than that of other oxidants and absorbents.…”
Section: Reaction Kineticsmentioning
confidence: 70%
“…In previous research, the apparent activation energies of the NO removal using a NaClO 2 solution, an H 2 O 2 /Na 2 S 2 O 8 strong alkali solution, and an H 2 O 2 /NaOH solution were 42.5, 26.3, and 27.8 kJ/mol, respectively. [21][22][23] These results show that the apparent activation energy of the NO removal by wet scrubbing using the oxidative absorbent S 2 O 8 2-/CaO 2 is higher than that of other oxidants and absorbents. It is likely that the NO removal reactions of the gas-liquid-solid phases coexisted in the oxidative absorbent (S 2 O 8 2-/CaO 2 ) system.…”
Section: Reaction Apparent Activation Energymentioning
confidence: 93%